Evaluation and Validation of a Semiautomatic Image Analysis Method: Quantification of Nares Cell Proliferation of Rhinella arenarum (Anura) Detected with the Avidin-Biotin Complex/Peroxidase, DAB. (4th March 2015) - Diaz Zamboni, Javier Eduardo; Osella, Daniela; Paravani, Enrique Valentín; Casco, Víctor Hugo
Abstract : The current report presents the development and application of a novel methodological approach for computer-based methods of processing and analysis of proliferative tissues labeled by ABC-peroxidase method using 3, 3′-diaminobenzidine (DAB) as chromogen. This semiautomatic method is proposed to replace the classical manual approach, widely accepted as gold standard. Our method is based on a visual analysis of the microscopy image features from which a computational model is built to generate synthetic images which are used to evaluate and validate the methods of image processing and analysis. The evaluation allows knowing whether the computational methods applied are affected by the change of the image characteristics. Validation allows determining the method's reliability and analyzing the concordance between the proposed method and a gold standard one. Additional strongness of this new approach is that it may be a framework adaptable to other studies made on any kind of microscopy.